Pengaruh Fee Audit, Ukuran KAP, dan Workload terhadap Kualitas Audit: Studi Empiris pada Perusahaan Sektor Keuangan - Wikky Lendika Putra; Nelvirita Nelvirita (Jurnal Eksplorasi Akuntansi, 2022)
This research examines the association of audit fees, Public Accounting Firm Size, and Workload as independent variables on audit quality. This research was conducted at financial sector company listed on the Indonesia Stock Exchange from 2018-2020. This research is important to do considering the literature review shows inconsistent results on each research variable. The research sample was selected through purposive sampling method and using logistic regression as the basis of analysis.The results of the research and hypothesis testing that have been carried out show that the first hypothesis is accepted where there is a significant negative effect between workload and the quality of the audit results. The results of the research and hypothesis testing that have been carried out show that the first hypothesis is rejected where there is no influence between audit fees and the quality of audit results. the second hypothesis is rejected where there is no influence between the size of the auditor's public accounting firm on audit quality. the third hypothesis is rejected where there is no influence between workload on audit quality.